Impact of Heat on Human and Animal Health in India: A Landscape Review - Sandul Yasobant; K. Shruti Lekha; Poonam Trivedi; Shruti Krishnan; Chinmayee Kator; Harleen Kaur; Mudita Adaniya; Anish Sinha; Deepak Saxena (Dialogues in Health)
Climate change presents a significant global public health challenge for animals and humans. Due to geography, climate, population, and urbanization, India is vulnerable to extreme heat. This review aims to explore the impact of heat on human and animal health in India. The publications on this topic were retrieved from PubMed and Google Scholar using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Out of 219 articles extracted, 44 were reviewed. The review included articles published in the last ten years, regardless of design. Half of the 44 articles were original studies; the rest were perspective, opinion, review studies, editorial, or commentary papers. The present review shows how heat adversely affects human health, increasing mortality and morbidity, especially during heat waves. Heat-related health issues in India include increased hospital admissions for cardiorespiratory diseases, mental health problems, reduced productivity, and agricultural yields. Vulnerable groups like workers, pregnant women, and children require targeted interventions. Limited evidence exists on the impact of heat on animals, but studies show increased health problems due to high temperatures. Targeted interventions are needed to prevent heat-related mortality and morbidity in India.